2000
DOI: 10.1046/j.1469-7580.2000.19740635.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of development of desmin‐positive hepatic stellate cells in mouse liver

Abstract: Development of desmin-positive hepatic stellate cells was studied in mice using double immunofluorescent techniques and in vitro cultures with special attention given to their cell lineages. Several studies recently reported on the presence of cells that are immunologically reactive with both antidesmin and anticytokeratin antibodies in young fetal rat livers, and suggested the possibility that these cells give rise to hepatocytes and hepatic stellate cells. At early stages of mouse liver development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 41 publications
2
35
1
1
Order By: Relevance
“…Desmin has been shown to be a marker for stellate cell differentiation. 39 This result is further confirmed by colocalization of Foxf1 expression with GFAP staining in adult liver. Although stellate cells have been suggested to arise from either the septum transversum mesoderm 15 or the neural crest cells, 16,17 our studies suggest that a subset of stellate cells are derived from the septum transversum mesenchyme.…”
Section: Discussionsupporting
confidence: 70%
“…Desmin has been shown to be a marker for stellate cell differentiation. 39 This result is further confirmed by colocalization of Foxf1 expression with GFAP staining in adult liver. Although stellate cells have been suggested to arise from either the septum transversum mesoderm 15 or the neural crest cells, 16,17 our studies suggest that a subset of stellate cells are derived from the septum transversum mesenchyme.…”
Section: Discussionsupporting
confidence: 70%
“…As shown previously, E-cadherin is specifically expressed in hepatoblasts (22,23). Nitou et al (23) isolated E-cadherinϩ cells from E12.5 mouse liver by using Dynabeads and enriched E-cadherinϩ cells to 98% purity.…”
Section: Discussionmentioning
confidence: 99%
“…Dlkϩ cells from E14.5 mouse fetal liver were able to differentiate into both hepatocytes and biliary epithelial cells in vitro (42). Recently, E-cadherin has been shown to be a specific cell surface marker for hepatoblasts (22,41). Nitou et al (23) indicated that E-cadherinϩ cells isolated from E12.5 mouse liver require coculture with cells of the E-cadherin-negative fraction, which includes endothelial and mesenchymal cells, for their survival and differentiation in vitro (23).…”
Section: Cd49fmentioning
confidence: 99%
“…Desmin could be regarded as a marker of HSC [14] , and α-SMA as the marker of activation of HSC [15] . α-SMA is a kind of filament protein which is about 7 nm in diameter and mainly exists in smooth muscle cells as a portion of cytoplasm framework and a functional unit of cell contraction.…”
Section: A B a Bmentioning
confidence: 99%